Frequency of Obesity and Dyslipidemia in The Patients with Hypothyroidism (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Hypothyroidism is a common endocrine disorder resulting from deficiency of thyroid hormone. Thyroid hormones have regulatory function on different metabolism in human. Hypothyroidism can lead to changes in lipid profile and BMI of people. The objective of the study was to evaluate the frequency of obesity and dyslipidemia in hypothyroid patients.Objective: To evaluate the frequency of obesity and dyslipidemia in hypothyroid patients.Materials and Methods: This was an observational cross-sectional study among purposively selected 96 patients diagnosed as hypothyroidism at Medicine and Endocrinology Department of Dhaka National Medical College & Hospital from August 2017 to September 2018. Analysis was done using the analytic software SPSS version 21.0.Results: Age of the patients ranged from 21 to 60 years with a mean of 39.2+9.5 years. Majority of the patients were female (86.5%) and housewives (71.9%), belongs to middle class society (89.6%), age of the highest number of the patients were in 31-40 years of age group (37.5%). In the study, TSH (59.4%), FT3 (87.5%) and FT4(86.5%) level was within normal range, categorized as subclinical hypothyroidism 86.5% of patient. BMI found as obese in majority of the patient, among them category I obesity, category II obesity and category III obesity were 46.9%, 32.3% and 5.2% respectively. Laboratory test results for lipid profile showed majority of the patient had desirable level of total cholesterol (62.5%), triglyceride level higher than normal level includes High level of triglyceride (33.3%) and Hypertriglyseridemic (39.6%). LDL cholesterol level was higher in more than half of the better outcome of patients comprising Near/above optimal, Borderline high, High and Very high. Majority (71.9%) of them had normal level of HDL cholesterol.Conclusion: Subclinical hypothyroidism is more prevalent in the patients. Higher proportion of them have elevated level of triglyceride and LDL cholesterol. Obesity is more common in hypothyroidism patients. Proper management of dyslipidemia and obesity is recommended for the patients with hypothyroidism.J. Dhaka National Med. Coll. Hos. 2023; 29 (01): 20-24